Participation in Scientific Activities as a Driver of Sustainable Nursing Education: An Educational Management Perspective from Minahasa Regency, Indonesia - Selvie Serly Rumagit; Orbanus Naharia; Joulanda A M Rawis; Arie F. Kawulur (JR Education, 2026)
Continuing nursing education is a crucial element in maintaining nurses' professional competence amidst the dynamic development of health sciences and demands for quality services. One form of implementation of continuing professional development is participation in scientific activities such as seminars, workshops, and training, which play a role in updating knowledge and improving clinical practice skills. However, nurses' involvement in scientific activities is determined not only by individual motivation but also by the support of the educational management system within healthcare organizations. This study aims to analyze how nurses' participation in scientific activities contributes to the sustainability of nursing education from an educational management perspective in Minahasa Regency. The results indicate that participation in scientific activities is an important indicator in strengthening the ecosystem of continuous professional learning, especially when supported by organizational policies, educational leadership, and access to competency development programs. This finding aligns with global studies that confirm that continuing professional development has a significant relationship with improved clinical competence, service quality, and patient safety. Furthermore, institutional support and a learning organizational culture have been shown to play a role in increasing nurses' engagement in professional development activities. Thus, participation in scientific activities should be viewed as an integral part of a continuing nursing education management strategy that is oriented not only toward improving individual competence but also toward strengthening the professional education system within the context of regional healthcare services.